Protective effect of corncob extract cream on guinea pig (Cavia porcellus sp) skin pigmentation exposed to ultraviolet B (UVB) rays - Harlisa, Pasid; Puspitasari, Indah Wahyu; Yuliyanti, Suryani (Universitas Gadjah Mada, 2023)
Ultraviolet B (UVB) rays exposure causes skin inflammation and pigmentation lead to decrease skin lightness. Corncobs (Zea mays) contain flavonoids which can act as antioxidant to prevent free radicals and protect the skin pigmentation. This study aimed to evaluate the protective effect of corncob extract cream on skin pigmentation exposed to UVB rays. This pre-posttest control group study was applied to 25 guinea pigs (Cavia porcellus sp) randomly divided into five groups. Corncob extract cream was given every day 20 min before and 4 h after UVB exposure. The UVB exposure total dose was 780 mJ/cm2. Mexameter examination was carried out on the 1st day and 28th day after treatment. There were significantly differences in the lightness level and the mean melanin index (MI) difference of guinea pigs before and after intervention on various groups (p<0.05). No significantly different of the MI between pre- and post-treatment was observed on normal control group (0.22) and negative control group (-1.06) (p>0.05). However, significantly different of the MI was observed on positive control group (-4.01), corncob 40% group (-2.72), and corncob 30% group (-2.03) (p<0.05). In conclusion, corncob extract cream can inhibit the skin pigmentation due UVB rays exposure.